The Politics of Pulpit Religiosity in the Era of Covid-19 in Kenya - Kilonzo, Susan M.; Omwalo, Bryson O. (Frontiers in Communication, 2021)
This essay centres on the role of religion in the era of Covid-19. We juxtapose social media and religious practices in a way that challenges the conventional religion of the pulpit to deconstruct the myths and misconceptions around spirituality in the era of Covid-19. We show the transformation of worship from physical worship places, particularly churches, to virtual engagements through social media. Through observation, close relations’ accounts, personal experiences and media perspectives, we analyze the politics that surrounded religious observances in the first seven months of Covid-19 pandemic in Kenya. We make a case that, discoveries made in these seven and other months to come, will most likely influenced the myths and misconceptions about religion and religious practices in the Country. From these accounts, we project a future that is likely to reap from the benefits of technology, and especially social media, which has revolutionized exchange of ideas, sermons, prayers and music We challenge the very notion of pulpit religiosity, and the myths and misconceptions that religion cannot be without physical fellowships.